Spatial relational memory requires hippocampal adult neurogenesis - Dupret, D; Revest, J; Koehl, M; Ichas, F; De Giorgi, F; Costet, P; Abrous, D; Piazza, P (Public Library of Science, 2008)
The dentate gyrus of the hippocampus is one of the few regions of the mammalian brain where new neurons are generated throughout adulthood. This adult neurogenesis has been proposed as a novel mechanism that mediates spatial memory. However, data showing a causal relationship between neurogenesis and spatial memory are controversial. Here, we developed an inducible transgenic strategy allowing specific ablation of adult-born hippocampal neurons. This resulted in an impairment of spatial relational memory, which supports a capacity for flexible, inferential memory expression. In contrast, less complex forms of spatial knowledge were unaltered. These findings demonstrate that adult-born neurons are necessary for complex forms of hippocampus-mediated learning.